Frequency of anemia in children at discharge from a pediatric intensive care unit of Pakistan - Kamran, Zainab; Lohana, Sujjata; Aijaz, Mohammad Sartaj; Umer, Syed Muhammad; Waqas, Muhammad; Haque, Anwarul (International Journal of Contemporary Pediatrics, 2025)
Background: Anemia in critically-ill children is reported in one-third to three-fourth at admission and during stay in Pediatric Intensive Care Units (PICU). Limited data is available on anemia in children at discharge from PICU (post-PICU anemia). To determine the prevalence of anemia in critically-ill children discharged from a PICU of public-sector Children hospital. Methods: A descriptive, retrospective cohort study was conducted on children (1mo-15 years) who had more than one hemoglobin (Hb) value measurement and last one was done within 24-hour of discharge in the PICU from January to December 2024. Anemia is defined as Hb <10 g/dl and severe anemia was Hb <7g/dl. Data like age, gender, admitting diagnosis and Hb prior to discharge were recorded. Results: A total of 457 patients met the eligibility criteria. The median age at admission was 10 (IQR 5.0-24.0) months, and 57.5% (n=263) were male. The most common admitting diagnoses were respiratory illnesses (52.7%, n=241), followed by infections related illnesses (23.2%, n=106), and neurological disorders 17.3% (n=79). At admission, 259 patients (56.7%) had anemia, of whom 35 (13.5%) had severe anemia (Hb <7 g/dl). At the time of discharge, anemia was present in 288 patients (63%), including 13 patients (4.5%) with severe anemia. Only 14.6% (29) developed anemia during PICU stay. However, there were fewer patients have severe anemia at discharge than at admission. Conclusions: Nearly two-third of critically-ill children have anemia at discharge from a PICU of low-middle income countries. More studies required to analyze post-PICU anemia to prevent significant reversible morbidity associated with it.